Cardiac abnormalities in children with congenital hyperinsulinism [CHI]. (4th April 2011) - Petkar, A; Jones, C; Ciotti, G; Rigby, L; Didi, M; Blair, J; Patel, L; Ehtisham, S; Clayton, P; Banerjee, I; Skae, M
Abstract : Congenital hyperinsulinism of Infancy (CHI) can be associated with cardiac problems such as septal hypertrophy and reversible hypertrophic cardiomyopathy1 2 however, the prevalence and range of cardiac abnormalities in CHI has not been well investigated. Aims and methods: With National Research Ethics Service approval and consent, we retrospectively reviewed the prevalence of cardiac abnormalities in 48 children with CHI. 43 patients were genotyped for potassium channel (KATP) mutations. Echocardiography was used to detect structural abnormalities and parameters for left/right/biventricular hypertrophy (LVH/RVH/BVH) that is, interventricular septal thickness in diastole (IVSd) and left ventricular posterior wall diameter (LVPWd) were used to quantify cardiac dysfunction, with serial echocardiography to assess cardiac improvement. ECG were used to corroborate muscle hypertrophy. Results: In our cohort of 48 children, 94% (45/48) required diazoxide therapy for CHI management and 48.8% (21/43) had positive KATP mutations. Median age at echocardiography was 23 days (5 days to 10.8 years). Cardiac structural abnormalities were present in 15 (31%) (five patent ductus arteriosus, four atrial septal defect, two ventricular septal defect, two branch pulmonary artery stenosis, one aortic stenosis and one aberrant subclavian artery). Myocardial hypertrophy was present in 29(60%) [23 LVH, 1 RVH, 5 BVH]. Z scores for LVPWd and IVSd were more than 2SD above mean in 51% and 48% of patients respectively. ECG abnormalities consistent with myocardial hypertrophy were present in only 24% (5/21). Cardiac medications (diuretics, digoxin, β blockers) were required in seven (15%), with improved function and discontinuation of therapy in six (75%). No significant associations were found between birthweights, genotypes and cardiac defects using χ 2 analysis. Conclusion: Our results show that 60% of CHI patients had echocardiographic evidence of myocardial hypertrophy and 15% (7/48) with myocardial hypertrophy at baseline required cardiac supportive treatment with reversal of pathology in 75% (6/7). About a third of patients had cardiac structural abnormalities. We advocate early cardiac assessment in infants with CHI, with baseline echocardiography as the investigation of choice.